The perceptions of lecturers and on-campus students on online teaching and learning in higher education - Chin, Kum (Curtin University, 2004)
In recent times, there has been a strong push for higher education institutions to offer more online courses to cater for students who otherwise would be denied university education. While this may benefit the many distance education students, the take-up rate of totally online education by current on-campus students remains uncertain. At the same time, many lecturers have started to design and develop online teaching material for their courses; many do so without the support of their employer - the university that they work in. The purpose of this study is two-fold. Firstly, to gain an insight into how on-campus students perceive online learning and to examine their readiness and willingness to make the shift from conventional classroom learning to online learning with no face-to-face contact. Secondly, to gain an insight into how lecturers approach online teaching; so as to better understand the problems they face when switching to a teaching mode that is quite different from the classroom teaching they are familiar with. The outcomes of this study will provide us with a better understanding of how lecturers and on-campus students perceive online teaching and learning. Understanding students' level of readiness to take part in online learning and their willingness to switch from the conventional classroom to cyberspace will assist universities in making decisions on the future direction of online courses. This is particularly important to those universities that intend to replace conventional classroom teaching with online courses. A better understanding of the problems faced by students and lecturers in online teaching and learning will also enable university administrators to ensure adequate resources are being allocated and the right level of support is provided.Lecturers' experiences in designing and developing online courses also assist in forming guidelines, policies and procedures for others to follow. An exploratory study was carried out on five groups of students and their lecturers to investigate their perceptions of online teaching and learning. Each group of students was enrolled in a specific subject unit when the study was carried out. All of the students were studying on-campus pursuing bachelor or postgraduate qualifications in various disciplines across the university. Students from each group were asked to complete a questionnaire during one of their lecture sessions. Their lecturers were interviewed individually. Both quantitative and qualitative analyses were applied on the collected data. Results of the study found that the majority of the students had sufficient knowledge at using the Internet and were very positive about online teaching and learning. While they would have liked to see more online teaching and learning used in their courses, they would not want it to replace classroom teaching and learning. The lecturers felt that online teaching - the development of online course material and the constant monitoring of students progress, was a time consuming but rewarding task. They would like to see their efforts in taking up such challenges recognised and rewarded by their institution and more resources be provided to assist them in further development in the area.In conclusion, the outcomes of this study show that if given the choice, not all oncampus students would like to enrol in online courses. The majority of them would still prefer classroom learning supplemented by online learning. Universities should invest in online teaching and learning with more resources allocated to assisting lecturers in online teaching. However, universities contemplating using online courses to replace traditional classroom teaching may find themselves losing their existing on-campus students.